Vulnerable Plaque to Vulnerable Patient: The Shifting Paradigm - Rahman, Mohammad Walidur; Ahmed, Chaudhury Meshkat (University Heart Journal, 2025)
Abstract not avaiable University Heart Journal 2024; 20(2): 47-48